The Effect of Home Training with Electropalatography A Post-operative Cleft Palate Patient with Residual Articulation Problems - YAMAMOTO, Ichiro; FUJIWARA, Yuri; INOUE, Miyuki (Journal of Japanese Cleft Palate Association, 2006)
Primary objective: To determine the effectiveness of electropalatography (EPG) home training using a portable training unit (PTU) for a patient with residual articulation disorders. Methods and procedures: The subject was a post-surgical bilateral cleft palate patient whose velopharyngeal function was adequate. She started EPG home training at the age of 8 years 4 months, because she had residual articulation disorders such as palatalized or lateral misarticulation, although she had received conventional speech therapy for more than 4 years. The WinEPG system (Articulate Instruments, Edinburgh) was used to make recordings during the initial assessment and the monthly follow-up. Experimental interventions: A training program was developed at each session, and she was instructed to carry out her homework assignments using the PTU. Main outcome: After 13 months of home training, marked changes in the EPG patterns and‘ Center of Gravity: COG’ values were observed. Conclusions: Compared to conventional therapy, EPG home training resulted in a much quicker improvement in target sound production.